Truth and the Phenomenological Landscape of Perception - Majka, Wojciech (Respectus Philologicus, 2012)
The main objective of the article is to present the phenomenological understanding of the idea of truth (alētheia). In the Heideggerian sense, alētheia is not limited to the traditional rendering of truth as coherence or correspondence. In other words, truth is not restricted to the appropriate or inappropriate ways of the representation of given aspects of cognitive experience. Instead, truth comes close to the notion of perception in the sense that it refers to the general way in which the world is unconcealed to human understanding. Of course, the adopted approach asks us to bracket the subject/object division that stands behind traditional metaphysical thinking ever since the time of Plato. In other words, the subject is not the starting point of experience; rather, the subject is a passive recipient of the kind of being-in–the-world—to use Merleau-Pontyian terminology—that is extending around it. Accounting for the phenomenological understanding of truth obliges us also to look at language not in the representative sense, but rather to regard it as the essencing of the vocabulary of being through which the world is revealed. This means that language is not just an abstract sign system based on the relation of signified—signifier in the Saussurian sense, but the ontological position from which we perceive the world and our existence in it.